2007
DOI: 10.1107/s1600536807029583
|View full text |Cite
|
Sign up to set email alerts
|

A cofacial binuclear copper(II) complex with a bridging 1,4-dithiane ligand

Abstract: Key indicators: single-crystal X-ray study; T = 120 K; mean (C-C) = 0.005 Å; R factor = 0.050; wR factor = 0.110; data-to-parameter ratio = 12.7.The molecule of (-1,4-dithiane-2 , lies on an inversion center, with a CuÁ Á ÁCu distance of 8.130 (1) Å . The Cu II centers have square-pyramidal coordination geometry, with Cu-O distances in the range 1.905 (2)-1.925 (2) Å and a Cu-S distance of 2.8088 (10) Å . The host binuclear complex is distorted from a rectangular shape. The inversion symmetry of the molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…[{Cu 2 (L 1 ) 2 } 2 (thiomorph) 4 ]•3thiomorph. Both the C (18) and C (21)-containing tertiary butyl groups are disordered over two positions and each was modelled with identical thermal parameters. The encapsulated thiomorpholine ligand is disordered across a symmetry position in two equal occupancy positions.…”
Section: Crystallographymentioning
confidence: 99%
See 1 more Smart Citation
“…[{Cu 2 (L 1 ) 2 } 2 (thiomorph) 4 ]•3thiomorph. Both the C (18) and C (21)-containing tertiary butyl groups are disordered over two positions and each was modelled with identical thermal parameters. The encapsulated thiomorpholine ligand is disordered across a symmetry position in two equal occupancy positions.…”
Section: Crystallographymentioning
confidence: 99%
“…3 We, and others, have found that ligands incorporating more than one β-diketone motif react with selected metal ions to yield an array of metallo-supramolecular architectures with the products in many instances exhibiting a significant degree of predictability. 1,3,10 Structures generated with these ligands include helicates, [11][12][13][14] tetrahedra, 15,16 boxes, 17 capsules 18 and an unprecedented universal 3-ravel; 14 for example, the well defined coordination vectors of ligands L 1-3 produce neutral planar metallocyclic species of type [M 2 (L 1 ) 2 ] (1) 11,13,[19][20][21] [M 3 (L 2 ) 3 ] (2) 16,22 and the larger [M 3 (L 3 ) 3 ] (3) 23,24 upon reaction with selected divalent transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating two donor atomsinto a cyclic compound offers an additional level of confinement that might give rise to interestingc oordination patterns.1 ,4-Dichalcogeno derivatives of cyclohexane appeared as interesting bondingp artnersa st he variation in conformation could easily turn them from mono-into bidentate ligands. 1,4-Dithiane was chosen to act as astarting point in an upcoming study about the coordination behaviour of the aforementionedc ompounds as it has been found to realize avariety of coordination modes: it has been found to act as ap urely monodentate ligand [1], as a monodentate, m 1 bridging ligand [2],asamonodentate, m 2 bridging ligand [3] and as bidentate chelating ligand [4].I ts crystal structurehas been reported earlier, however,atroom temperature only with [5]and without [6] hydrogen atom positions localized or as aprivate communication at low temperature [7]sothat no discussion of metricalparameters is at hand forthese latter conditions. The present study is intended to close this gap and to enable the comparison of metrical parameters in envisioned coordination compounds whose structures will be determined at low temperature as well.…”
mentioning
confidence: 99%